ON SYMMETRY REDUCTIONS AND INVARIANT SOLUTIONS OF THE k-ε TURBULENCE MODEL - N. G. Khor'kova (Научный вестник МГТУ ГА)
Methods of theoretical group analysis of differential equations are applied to the k -ε turbulence model. Symmetry reductions of the k -ε turbulence model with respect to some three-dimensional symmetry subalgebras are considered. Families of exact solutions are obtained.